Economic policy uncertainty of China and investment opportunities: a tale of ASEAN stock markets - Mohd Thas Thaker, Hassanudin; Mohd Thas Thaker, Mohamed Asmy; Sakti, Muhammad Rizky Prima; Sifat, Imtiaz; Allah Pitchay, Anwar; Iqbal Hussain, Hafezali (Emerald Publishing Limited, 2022)
Purpose – The purpose of this paper is to examine the effect of economic policy uncertainty (EPU) of China on investment opportunities in five ASEAN economies. Design/methodology/approach – This paper employs advanced empirical approaches, such as Multivariate DCC-GARCH and Continuous Wavelet Transform (CWT) to test the research objective. The period of analysis involved monthly data from 2003 until 2019. Findings – This paper provides evidence where the Malaysian stock market to be the least exposed to risks emanating from Chinese EPU, followed by Singapore, the Philippines, Thailand and Indonesia. Results for investment opportunities based on time horizon suggest, for a short-term holding period, investors are better off investing in Singapore and Indonesia, while, for medium-term holding periods, all ASEAN markets appear lucrative except for the Philippines.